La legislación censoria española en los siglos XVI-XVIII - Álvarez García, Héctor (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2010)
The subject of this article is to study the excessively meticulous censorial legislation enacted in the XVI-XVIII centuries by the House of Austria and Bourbon; as well as the causes of the Central Power failing to implement it, and the significant role performed by the Inquisition with a view to controlling freedom of expression in national and foreign works, bearers of heretical and revolutionary doctrines, aimed at subverting the political-religious order of the Old Regime.